Traditional foods from Black Sea region as a potential source of minerals - Albuquerque, T.G. (2014)
BACKGROUND: In the past few years, minerals have assumed great importance in public health. As a consequence, considerable research has been carried out to better understand their physiological role and the health consequences of mineral-deficient diets, to establish criteria for defining the degree of public health severity of malnutrition, and to develop prevention and control strategies. In most countries, there is limited information on the mineral content of traditional foods, and consequently it is very difficult to estimate mineral intake across these countries. RESULTS: Ten minerals were quantified in 33 traditional foods from Black Sea area countries. Our results indicate a considerable variability among the analysed traditional foods; nevertheless, the most abundant components were sodium (ranging from 40.0 to 619 mg 100 g−1, for kvass southern and herbal dish, respectively), potassium (varied between 45.5 mg 100 g−1 for millet ale and 938 mg 100 g−1 for roasted sunflower seeds), and phosphorus (22.2 mg 100 g−1 and 681 mg 100 g−1 for sauerkraut and roasted sunflower seeds, respectively). CONCLUSION: This is the first study that provides validated data on the mineral content for 33 traditional foods from Black Sea area countries, which is important in order to elucidate their role in the dietary pattern of populations and to preserve and promote these foods.